Influence of mechanical activation and heat treatment on magnetic properties of nanostructured mixture Ni85.8Fe10.6Cu2.2W1.4 - Vasić, Milica M; Kalezić-Glišović, Aleksandra S; Milinčić, Radovan; Radović, Ljubica; Minić, Dušan M; Maričić, Aleksa M; Minić, Dragica M. (Journal of Mining and Metallurgy, Section B: Metallurgy, 2019)
The mechanical activation of the Ni85.8Fe10.6Cu2.2W1.4 powder mixture in the time intervals of 30-210 min in combination with thermal treatment at 393-873 K resulted in microstructural changes, forming the nanostructured mixture of the same composition but improved magnetic properties. The best result were achieved for mechanical activation during 120 min and thermal treatment at temperatures close to the Curie temperature (693K), enhancing the mass magnetization of the starting powder mixture by about 57%. The microstructural changes involving the structural relaxation, decrease in free volume, density of dislocation and microstrain, improve structural characteristics of material, enabling better mobility of walls of magnetic domains and their better orientation in applied magnetic field and consequently enabling better mass magnetization of the material. With longer time of milling, the growing stress introduced in the sample undergoes easier relief, relocating stress-relieving processes toward lower temperatures.